Assessment of Organic Pollution Risks in Groundwater of the Al-Ajilat Region, Libya (Al-Farooq Journal of Sciences, 2026)
This study was conducted to assess the risks of organic pollution in groundwater wells located in the Al-Ajilat region, Libya. A total of ten groundwater samples were collected and analyzed. The results showed that some groundwater wells, namely A3, A4, A5, and A6, exhibited nitrate concentrations exceeding the maximum permissible limit of 45 ppm specified by the Libyan Drinking Water Standards (1992). This increase may be attributed to the proximity of these wells to unlined septic pits and, in general, to the geological characteristics of the aquifer.Furthermore, wells A4, A5, A6, A7, A8, A9, and A10 recorded Biochemical Oxygen Demand (BOD) values exceeding the maximum permissible limit of 6 ppm. This is likely due to the hydraulic connection between these wells and a nearby deep septic well (BW), resulting in groundwater contamination and rendering the water unsuitable for drinking.Regarding Chemical Oxygen Demand (COD), wells A4, A7, A8, A9, and A10 exceeded the maximum allowable limit of 10 ppm according to the Libyan Drinking Water Standards (1992). In addition, Escherichia coli (E. coli) counts of 109, 112, and 100 were recorded in wells A4, A6, and A9, respectively, indicating microbial contamination of the groundwater in these wells.
Keywords: Groundwater Quality; Organic Pollution; Nitrate; Biochemical Oxygen Demand (BOD).